The Effect of Marketing Communication Strategies Through Celebgrams on Perceptions of the Product among Indonesian Millennials - Zein, Duddy; Wagiati (Jurnal Komunikasi, 2023)
The rapid growth of social media has opened up vast opportunities for companies to capture the attention of potential customers. In this context, it has become imperative for brands to adapt their strategies to effectively target millennials through social media platforms. Notably, brands in the fashion industry have increasingly relied on online "celebrities" or influencers of social media (ISMs), commonly referred to as celebgrams on Instagram, to disseminate information and enhance consumer awareness of their products. This article aims to investigate the impact of celebgram endorsements on consumer perceptions of products by examining social comparatives and personal conformity. Experimental research was conducted with three conditions: celebgram, brand, and surveillance. Through a comprehensive questionnaire consisting of forty-eight questions related to celebgram, personal conformity, social comparative, and product perceptions, data was collected from a sample of 50 participants. The results revealed a significant correlation between the source of advertisement uploads and consumer perceptions of the products. Moreover, a relationship was found between personal conformity, social comparative factors, and perceptions of both celebgrams and the endorsed products. These findings highlight the substantial influence of the source of posts on consumers' perception of the products. Additionally, the research demonstrates that consumer perceptions of celebgrams play a pivotal role in shaping their perceptions of the endorsed products. These research findings have practical implications for marketing communication professionals utilizing social media platforms. By understanding the impact of celebgram endorsements on consumer perceptions, marketers can devise effective strategies to leverage social comparatives and personal conformity to enhance product awareness and influence consumer behavior.